The recent weathering of uraninite from the Cervena vein, Jachymov (Czech Republic): a fingerprint of the primary mineralization geochemistry onto the alteration association - Plasil,J.; Sejkora,J.; Skoda,R.; Skacha,P. (Journal of Geosciences, 2014)
Uraninite and the supergene minerals from the Cervena hydrothermal uranium vein (Jachymov ore district, Czech Republic) were studied. These supergene minerals represent alteration products of the joint weathering of uraninite and hypogene sulfide minerals, connected to the acid-mine drainage (AMD) systems. The complex geochemistry of the hypogene mineralization provided a unique environment for formation of chemically diverse supergene phases. Among other features, the weathering system is characterized by the high activity of Cu2+ and REE, which control the composition of the resulting supergene minerals: commonly occurring are Cu-dominant uranyl sulfates of the zippeite group (pseudojohannite, Cu-rabejacite), Cu-dominant uranyl silicates (cuprosklodowksite) or Y- and REE-containing uranyl sulfate mineral sejkoraite-(Y). The high activity of Cu2+ and REE is also reflected by the fact that both elements enter minerals, which are nominally Cu- or REE-free (marecottite, rabejacite, tyuyamunite, and compreignacite). The alteration association was evaluated with regard to the crystal-chemical properties of each mineral using the bond-valence approach, documenting distinct evolutionary trends during weathering.
Keywords: uraninite; supergene weathering; acid-mine drainage; mineral data; X-ray diffraction; bond-valence approach